EFFECTIVENESS OF USING INSTAGRAM AS A MEDIA FOR DISSEMINATION OF LEGAL INFORMATION IN THE DISTRICT PROSECUTOR'S OFFICE OF BOGOR REGENCY - Chelsya Eunike Rompas; Priatna (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to determine the effectiveness of Instagram's use as a medium for disseminating legal information at the Bogor Regency District Attorney's Office. The research used a descriptive qualitative approach through a case study method. Data were collected through in-depth interviews with account managers and members of the public, observations of official Instagram account activity, and documentation from archives and social media content. Data analysis employed the Miles and Huberman interactive model, which encompasses data reduction, data presentation, and conclusion drawing. The results indicate that Instagram is quite effective in conveying legal information to the public, particularly young people. Effectiveness is evident across cognitive, affective, and conative dimensions, although obstacles remain, such as limited human resources, less interactive content, and the lack of structured content evaluation. These findings confirm that social media, particularly Instagram, has significant potential to support the prosecutor's office's role in providing legal education while encouraging public participation in understanding legal issues.